Memory and comprehension deficits in spatial descriptions of children with non-verbal and reading disabilities - Mammarella, Irene C.; Meneghetti, Chiara; Pazzaglia, Francesca; Cornoldi, Cesare (Frontiers in Psychology, 2015)
The present study investigated the difficulties encountered by children with nonverbal learning disability (NLD) and reading disability (RD) when processing spatial information derived from descriptions, based on the assumption that both groups should find it more difficult than matched controls, but for different reasons, i.e. due to a memory encoding difficulty in cases of RD and to spatial information comprehension problems in cases of NLD. Spatial descriptions from both survey and route perspectives were presented to 9- to 12-year-old children divided into three groups: NLD (N=12); RD (N=12), and typically-developing controls (TD; N=15); then participants completed a sentence verification task and a memory for locations task. The sentence verification task was presented in two conditions: in one the children could refer to the text while answering the questions (i.e., text present condition), and in the other the text was withdrawn (i.e., text absent condition). Results showed that the RD group benefited from the text present condition, but was impaired to the same extent as the NLD group in the text absent condition, suggesting that the NLD children’s difficulty is due mainly to their poor comprehension of spatial descriptions, while the RD children’s difficulty is due more to a memory encoding problem. These results are discussed in terms of their implications in the neuropsychological profiles of children with NLD or RD, and the processes involved in spatial descriptions.